2018
DOI: 10.1002/ece3.4710
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced biparental care during colony foundation in two subterranean termites

Abstract: Parental care is a major component of reproduction in social organisms, particularly during the foundation steps. Because investment into parental care is often costly, each parent is predicted to maximize its fitness by providing less care than its partner. However, this sexual conflict is expected to be low in species with lifelong monogamy, because the fitness of each parent is typically tied to the other's input. Somewhat surprisingly, the outcomes of this tug‐of‐war between maternal and paternal investmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The efficiency of this second step of protist transmission, which was previously referred as the β component of transmission (i.e., the probability β ), was not studied and currently remains unknown. However, several recent studies conducted on R. grassei and other Reticulitermes species suggest that the probability β could be very high and even close to 1 (Brossette, Meunier, Dupont, Bagnères, & Lucas,; Shimada et al, ). These studies showed that the two primary reproductives founding an incipient colony have numerous opportunities to transfer their gut symbionts to the first larvae produced in the young colony.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The efficiency of this second step of protist transmission, which was previously referred as the β component of transmission (i.e., the probability β ), was not studied and currently remains unknown. However, several recent studies conducted on R. grassei and other Reticulitermes species suggest that the probability β could be very high and even close to 1 (Brossette, Meunier, Dupont, Bagnères, & Lucas,; Shimada et al, ). These studies showed that the two primary reproductives founding an incipient colony have numerous opportunities to transfer their gut symbionts to the first larvae produced in the young colony.…”
Section: Discussionmentioning
confidence: 98%
“…These studies showed that the two primary reproductives founding an incipient colony have numerous opportunities to transfer their gut symbionts to the first larvae produced in the young colony. Queens and kings keep their gut protists for quite a long period (Shimada et al, ) and regularly exhibit proctodaeal trophallaxis with their larvae (Brossette et al, ). This behaviour probably allows the transfer of most gut protists to the first cohort of workers, which in turn will propagate them by proctodaeal trophallaxis to all members of the colonies and thereby ensure the perpetuation of protists within the colony .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, R. flavipes and R. grassei are sympatric in the sampling area of the current study (Oléron) where they display differences in their life history traits. Both species exhibit extended families (i.e., the presence of multiple neotenic reproductives), but they differ in traits like parental care (Brossette et al, 2019), colony foundation (Brossette et al, 2017) and aggressiveness (Perdereau et al, 2011;Duarte et al, 2018). Feeding at multiple sites is a common trait for R. flavipes, while less than half of the colonies of R. grassei exhibit this trait in the studied population (Deheer et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Overall, our study highlights the greater short-term exploration capacity of the invasive species, R. flavipes, compared to the two other Reticulitermes species studied. Together with its capacity for developing numerous reproductives, reduced intraspecific aggression, rapid colony foundation, and elevated interspecific competitive ability (Perdereau et al, 2011;Brossette et al, 2017Brossette et al, , 2019, this enhanced exploration activity may promote its invasiveness. Greater exploration activity not only increases species dominance and facilitates the monopolization of resources, but also increases propagule pressure, which is an essential component of dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…Such losses are more common for some host species than others, and for some protist species than others (Kitade and Matsumoto, 1993;Kitade et al, 2013;Michaud et al, 2020). Protists are inherited biparentally: both king and queen contribute their symbionts to the nascent colony's microbial community (Shimada et al, 2013;Brossette et al, 2019). Host outcrossing can therefore allow complementation of these deficient communities, helping to maintain a consistent protist community across the host species' range (Michaud et al, 2020).…”
Section: Introductionmentioning
confidence: 99%